Gestão empreendedora no turismo: caso roteiro Caminhos de Santiago das Missões - RS - Marquetto, Rut Maria Friedrich (2007)
This research tried to identify the enterprising management features near by the entrepreneurs of the touristic route Caminhos de Santiago das Missões and develop a supporting methodology which contains a management pattern to be used as an intervention instrument at the referred route. This method contextualizes the economic, social, cultural and natural dynamics following processes that will have to be idealized and worked by actions that involve public and private organs as well as national organizations. The success of this kind of venture is closely related to the adequate use of management tools according to the place s environmental condition survey. Thus, it is support, inspired with interpretations and related to experiences which have already happened, so that it can enhance this interface understanding of the touristic phenomenon. The managers´pro-active view might be improved with this information and actions focusing on the coordination and organizational development, potentized. Through these reflexions, we hope to contribute for debates on matters of interprising management of the touristic activity